Associations between Environmental dust composition and Atopic Dermatitis in urban and rural settings. Issue 5 (16th March 2021) - Trikamjee, Thulja; Basera, Wisdom; Botha, Maresa; Facey‐Thomas, Heidi E.; Gaunt, Ben; Genuneit, Jon; Gray, Claudia L.; Hadebe, Sabelo; Hlela, Carol; Kirstein, Frank; Lunjani, Nonhlanhla; Mankahla, Avumile; et al.
Abstract: Background: Environmental exposures are involved in the pathogenesis of the allergic phenotype and in determining which individual triggers a person becomes sensitized to. Atopic dermatitis (AD) may modulate these effects through increased penetration through the skin modifying the immune system and AD may be triggered or intensified by environmental exposures. These exposures and immune‐modulating factors may differ in urban and rural environments. Objectives: To compare house dust composition in urban and rural settings and correlate them with AD outcomes. Methods: Dust samples were collected from the beds of 156 children aged 6 months to 3 years. 42% of participants had atopic dermatitis. Samples were analyzed for bacterial endotoxin, fungal (β‐1, 3‐glucan) levels, and house dust mite, cockroach, dog, cat, mouse, and peanut allergen. Exposures were compared in urban and rural environments and in participants with and without AD. Results: Endotoxin but not fungal β‐glucan exposure is higher in the environment of healthy controls than children with AD in both urban and rural settings. House dust mite allergen exposure is high in urban and rural settings with Dermatophagoides detected in 100% of samples. Cat and dog allergen exposure mirrors pet ownership patterns which differ slightly between groups and environments. Mouse allergen exposure is higher in urban homes. Conclusion: Environmental endotoxin may be protective against AD in both urban and rural settings. There are marked differences in allergen exposure in urban and rural settings, but these are unlikely to be important protective or risk factors.